2019
DOI: 10.1002/lary.28152
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal corticosteroids and saline: Usage and adherence in chronic rhinosinusitis patients

Abstract: Objective Intranasal saline irrigations and intranasal corticosteroids are supported by level‐1 evidence for medical management of chronic rhinosinusitis (CRS). We sought to study adherence with these medications. Methods Prospective study of 174 patients with CRS. Patients reported their usage of intranasal saline irrigation and intranasal corticosteroid over the preceding 3 months, at presentation, and a subsequent follow‐up visit 3 to 12 months later. Adherence was defined as reported medication usage for ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
(59 reference statements)
1
20
0
Order By: Relevance
“…[35][36][37][38] However, recent research has shown that patient adherence to saline irrigation and intranasal steroids are typically less than 25% and 50%, respectively. 39 Additionally, the duration of drugmucosa interaction of nasal sprays is typically less than a few hours secondary to ciliary clearance of the drug. 40 Low patient adherence combined with innately low mucosal-drug contact time dictates the need for alternative topical therapies that allow for prolonged therapeutic intervention without concern for patient nonadherence.…”
Section: A Rationale For Topical Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37][38] However, recent research has shown that patient adherence to saline irrigation and intranasal steroids are typically less than 25% and 50%, respectively. 39 Additionally, the duration of drugmucosa interaction of nasal sprays is typically less than a few hours secondary to ciliary clearance of the drug. 40 Low patient adherence combined with innately low mucosal-drug contact time dictates the need for alternative topical therapies that allow for prolonged therapeutic intervention without concern for patient nonadherence.…”
Section: A Rationale For Topical Therapiesmentioning
confidence: 99%
“…In addition, rinses can be done alone or in combination with topical steroid use, which has been shown to improve symptom burden 35‐38 . However, recent research has shown that patient adherence to saline irrigation and intranasal steroids are typically less than 25% and 50%, respectively 39 . Additionally, the duration of drug‐mucosa interaction of nasal sprays is typically less than a few hours secondary to ciliary clearance of the drug 40 .…”
Section: A Rationale For Topical Therapiesmentioning
confidence: 99%
“…[13][14][15][16] Perceived financial insecurity may lead to decisions that disrupt optimal care including medication nonadherence and inability to maintain necessary follow-up or multidisciplinary care. 15,17 This may also compromise surgical outcomes if patients do not adhere to medication and follow-up recommendations. 16 Understanding personal financial concerns can help guide healthcare providers when making recommendations regarding treatment.…”
Section: Introductionmentioning
confidence: 99%
“…16 Understanding personal financial concerns can help guide healthcare providers when making recommendations regarding treatment. 11,[15][16][17][18] In addition, engaging patients in shared decision-making, accounting for their financial concerns, may lend toward improved patient compliance and ultimately improved outcomes. 16,[19][20][21] The purpose of this study was to describe and evaluate how individual perceived financial burden may associate with personal cost-saving healthcare decisions that can impact quality of life (QOL) and outcomes in patients with self-identified sinusitis.…”
Section: Introductionmentioning
confidence: 99%
“…As in other respiratory diseases [3][4], adherence to treatment has been previously explored in CRSwNP, finding low use of INCS and abandonment [5]. Rudmik [8].…”
mentioning
confidence: 99%